MODEL BIMBINGAN KONSELING ISLAM BAGI SISWA TUNANETRA - A Said Hasan Basri; Hairunnisa BR Sagala (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2019)
Blind people as individuals who have limited vision have a risk or tendency to experience psychological problems as a result of their limitations. Thinking and treating as a weak person will actually worsen his condition. In fact there are many of them who reject it or not accept it, against the weakening of people who are physically normal, because they feel discriminated against in their lives. Likewise in education, they have the same desire as other normal individuals, want to get a decent education, and not be distinguished. The reality in inclusive schools has not yet led to ideal expectations. Therefore, there needs to be an intensive effort so that inclusive education for them can be as expected. One of them is through this kind of research. The purpose to be achieved in this study is to identify and describe the model of Islamic counseling that is appropriate for blind students.            The study was conducted with a qualitative approach in the MAN Maguwo inclusion school in Yogyakarta, involving two subjects of the BK teacher, and three subjects were blind students. The data collection techniques use interviews, observation and documentation.The result is that the Islamic guidance and counseling model used for blind students is to use the Nafsiah Islamic counseling model (internalization of religion in every attitude and behavior), Fardiyah (planting religious behavior) and Fi'ah (done in individual, group and classical), and contemporary, where there are five types, namely; constellation of services, development guidance, scientific guidance on activities aimed at, social reconstruction guidance, personal development guidance.